ANALISIS EFEKTIVITAS DAN EFISIENSI ANGGARAN KEGIATAN PADA BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN KABUPATEN SUMBAWA - K Kurniawansyah; Abdul Rahim; Jihan Faradila (Samalewa: Jurnal Riset & Kajian Manajemen, 2022)
This study aims to know the effectiveness and efficiency of budget management at Regional Personnel Education and Training Agency (BKPP) of Sumbawa District in fiscal year of 2021. The type of this study was quantitative descriptive study. The method used to collect data was through library method. The data used in this study was secondary data obtained from BKPP office of Sumbawa. To know the effectiveness of the existing budget in Regional Personnel Education and Training Agency in fiscal year of 2021, it was done analysis toward the budget of direct and indirect spending The results of study showed that the budget management at BKPP of Sumbawa District was very good. It was based on the realization of direct spending of 94.19% with ratio of "Effective". Meanwhile, the efficiency of indirect spending management was 97.85% with a ratio in the "Very Efficient" category.